Is the Sosiani River Healthy? Investigating the Relationship between Water Quality Indicators and Macroinvertebrate Assemblages in the Sosiani River - Nyakora, Oruta Joash (International Journal of Geography and Geology, 2016)
The health of rivers is of great concern to governments and communities worldwide due to their important ecological functions. Numerous studies have established that water quality indicators have a positive effect on river health. However, only a few studies have examined equatorial rivers, and, to date, there has been no study on the Sosiani River in Kenya. As such, this study explored the health of the Sosiani River by considering how its aquatic macroinvertebrate assemblages were affected by various water quality parameters. The research considered whether there was a relationship between water quality indicators and macroinvertebrate assemblages in the Sosiani River. This knowledge is of paramount importance to the communities and decision makers of the Sosiani catchment, and Kenya as a whole, since there is need to understand the relationship between the water quality indicators and the health of the river in order to allocate resources for its rehabilitation and maintenance. This study examined 10 sites, nine being “test” sites and one a “reference” site. The study established a significant relationship between water quality parameters and macroinvertebrate assemblages. The sites with natural riparian zone vegetation conditions were found to have more Ephemeroptera, Plecoptera, and Trichoptera macroinvertebrates when compared to those without or with exotic vegetation. In terms of absolute numbers of surface aquatic macroinvertebrates, sites characterised by dense stream bank vegetation had more macroinvertebrates than those characterised by forest with eroded, bare stream banks. From the study, it was therefore concluded that Sosiani River is healthier at head waters where there was natural forests compared to downstream where there was plantations, intensive farming and urban area. The study recommends that more detailed studies classify macroinvertebrates to gunus level and include microinvertebrates, since this may give a more accurate assessment of the river’s health. The study further recommends that identification keys for East African macroinvertebrates be developed.